Comparative In Vitro Evaluation of Commercially Available Pantoprazole Tablets - Mansoor, Saffar; Sharma, Rajeev; Dhakal, Sophia (Kathmandu University Journal of Science, Engineering and Technology, 2007)
Comparative study on in vitro evaluations (hardness, friability, weight variation, assay, disintegration, and dissolution tests) of marketed pantoprazole tablets (2 batches of each) from WHO GMP certified Nepalese companies (encoded with BP-02-A1, BP-02-A2), non-GMP certified Nepalese companies (encoded with BP-02-B1, BP-02-B2), and multinational companies (encoded with BP-02-C1, BP-02-C2) were done. The result of hardness, friability, weight variation, and assay and disintegration tests of all marketed products comply with pharmacopoeial limit. However, BP-02-A2 showed the fastest disintegration. Moreover, the comparison of percentage drug release of these companies on the basis of dissolution study demonstrated that BP-02-A2 (90 % drug release) complied best with standard RDRL protocol while BP-02-B2 (78% drug release) does not comply with above specification.